Accounting Ethics: From Professionals Views - Septiari, Dovi; Helmayunita, Nayang; Serly, Vanica (Jati: Jurnal Akuntansi Terapan Indonesia, 2023)
This research investigated the professional accounting perception about ethics. We used a semi-structured interview with 11 professional accountants that work as an auditor, tax consultant, financial accountant, and banker. The results show that accountants define ethics as rules and value. Several ethical problems like manipulation, profit management exploitation, and pressures leading to unethical actions were found in practice. The ethical value, senior's role, and corporate policy also play an essential role in helping accountants resolve ethical issues. This research has contributed to our knowledge about ethics perception from the professional perspective. Also, this finding gives important suggestions for the corporate, academics environment, and policymakers.